“You have a self-testing method that preserves privacy so how come you cannot give us treatment that does too?” Exploring the reasoning among young people about linkage to prevention, care and treatment after HIV self-testing in Southern Malawi - Lisa Harrison; Moses Kumwenda; Lot Nyirenda; Richard Chilongosi; Elizabeth Corbett; Karin Hatzold; Cheryl Johnson; Musonda Simwinga; Nicola Desmond; Miriam Taegtmeyer (BMC Infectious Diseases, 2022)
Abstract Background Young people, aged 16–24, in southern Malawi have high uptake of HIV self-testing (HIVST) but low rates of linking to services following HIVST, especially in comparison, to older generations. The study aim is to explore the barriers and facilitators to linkage for HIV prevention and care following uptake of HIV self-testing among young Malawians. Methods We used qualitative methods. Young people aged 16–24 who had received HIVST; community-based distribution agents (CBDAs) and health care workers from the linked facilities were purposively sampled from two villages in rural southern Malawi. Results We conducted in-depth interviews with thirteen young people (9 female) and held four focus groups with 28 healthcare workers and CBDAs. Young people strongly felt the social consequences associated with inadvertent disclosure of HIV sero-status were a significant deterrent to linkage at their stage in life. They also felt communication on testing benefits and the referral process after testing was poor. In contrast, they valued encouragement from those they trusted, other’s positive treatment experiences and having a “strength of mind”. CBDAs were important facilitators for young people as they are able to foster a trusting relationship and had more understanding of the factors which prevented young people from linking following HIVST than the healthcare workers. Young people noted contextual barriers to linkage, for example, being seen on the road to the healthcare centre, but also societal gendered barriers. For example, young females and younger adolescents were less likely to have the financial independence to link to services whilst young males (aged 19–24) had the finances but lacked a supportive network to encourage linkage following testing. Overall, it was felt that the primary “responsibility” for linking to formal healthcare following self-testing is shouldered by the young person and not the healthcare system. Conclusions Young people are happy to self-test for HIV but faced barriers to link to services following a self-test. Potential interventions for improving linkage suggested by this analysis include the establishment of youth-friendly linkage services, enhanced lines of communication between young people and healthcare providers and prioritising linkage for future interventions when targeting young people following HIVST.